Re-conceptualising sustainable development on the basis of the capability approach: A model and its difficulties - Ortrud Leßmann; Felix Rauschmayer (Helmholtz-Zentrum für Umweltforschung (UFZ), 2012)
This paper sketches a re-conceptualisation of sustainable development (SD) on the basis of the capability approach (CA). The notion sustainable development was developed as a compromise in a political process and has been re-interpreted (some say: diluted) again and again in the last 20 years. When modelling the notion through the lenses of the capability approach, difficulties occur that are at the core of SD and of CA or that are due to their combination. Our paper shows why it is not that easy to replace needs in the Brundtland definition of SD with capabilities. In our model, the differences between systemic and individual levels become clear and herewith the necessity to include both when dealing with issues of SD. The most salient difficulties relate to the multidimensionality and dynamics on both levels. Confronted to these difficulties, demanding individuals to consciously choose sustainable actions seems to be heroic. We propose two ways to alleviate the cognitive and moral burden on individuals by concentrating on the natural environment and by introducing collective institutions. Both alleviations are far from evident, though; this concerns their justification as well as their operationalization.
Keywords: 330; capability approach; sustainable development; systemic level; collective institutions; dynamics; Nachhaltige Entwicklung; Capability Approach; Theorie